Predictors of injuries among young players team games - Jarosław Domaradzki; Sebastian Chmielewski; Izabela Barbara Trojanowska; Dawid Koźlenia (Kazimierz Wielki University, 2018)
Introduction: The aim of the study was to determine the relationship between the basic somatic traits and the metric age and training experience of players and the injuries suffered. Material and methods: 125 male athletes aged between 14 and 19 years old were examined. They represented 4 sports disciplines. Respondents practicing American football (22 players), respondents playing football (30 players), respondents practicing handball (49 players), respondents practicing volleyball (24 players). All players belonged to the category of juniors. The research tool was a short questionnaire, in which the surveyed person gave their name and date of birth. The next part of the questionnaire contained questions about the sport practiced. The next stage of the study was the measurement of body height, which was performed with a Swiss anthropometer, and body weight was measured on electronic weight. The Body Mass Index (BMI) was calculated from the formula: body weight [kg]/height [m]2. Results: In all analysed sports, body weight is the most important for the number of injuries. BMI is important in all team sports. Slim body reduces the number of injuries by about 2-8 injuries. From among the analysed variables the body structure features have an influence on the number of injuries. There were no correlations between the age of competitors and their training experience. The number of injuries depends mainly on the body weight of the player. Conclusion: Football players suffered the most injuries during their career, followed by handball players. Average injuries of American football players and volleyball players were much lower and similar to each other. While analysing the whole group of the respondents, it was observed that among the variables discussed above, the weight of competitors has the strongest influence on the number of injuries suffered. The body weight has the strongest statistically significant effect on injuries in American football, and secondly in volleyball. The weakest, statistically insignificant, body weight affects injuries in footballers.